PERAMALAN PRODUKSI PADI KABUPATEN TUBAN - Muntiani Muntiani; Kresna Oktafianto (MathVisioN, 2023)
Tuban, which is an agricultural area, certainly has potential in the agricultural sector, namely food crops, especially rice production. However, what happened was that rice production could not keep up with the ever-increasing population growth rate. So, it is necessary to forecast the production of rice production in Kab. Tuban to anticipate the population that lacks rice production. The forecasting method used here is the Moving Average, Weight Moving Average and Exponential Smoothing and the forecasting results in 2021 are 6,716.058 tons.